KOMPETISI PRODUK PERKEBUNAN KELAPA SAWIT INDONESIA DENGAN NEGARA PESAING DI PASAR INTERNASIONAL - Danik Nurjanah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
This study aimed to determine the level of competition and the similarity of the export structure of Indonesian palm oil products with competing countries in the international market. Secondary data is used in this study which includes export data from Indonesia and its competitors (Malaysia, Thailand, Cambodia, and Colombia) in 2014-2020 sourced from UN Comtrade. Methods of Analysis to measure the level of competition in the trade of Indonesian palm oil products in the international market using the Export Overlapping Index (IEO) and the Export Similarity Index (ESI) are used to measure how much similarity is in the composition of exports of Indonesian palm oil products in the international market. The results showed that trade in palm oil products before and during the COVID-19 pandemic had a significant increase in the value of the level of similarity in exports from Colombia, Thailand, Malaysia, Cambodia. The highest level of competition for Indonesian palm oil exports is between Indonesia and Malaysia.